PELATIHAN PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN IPA BAGI KOMUNITAS BELAJAR MGMP IPA KABUPATEN PURWAKARTA - Indra Budiman; Rika Mulyati Mustika Sari; Lessa Roesdiana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
The goal of this community service program is to improve the teaching skills of junior high school science (IPA) teachers by teaching them a deep learning method that fits with the Merdeka Curriculum. The Science Teachers' Professional Learning Community (MGMP IPA) of Purwakarta Regency was the program's partner. The approaches used to put the plan into action included needs analysis, conceptual training, hands-on practice in making instructional materials based on deep learning with the use of artificial intelligence (AI), guided classroom implementation, and reflective evaluation. Data were gathered via pre-test and post-test questionnaires, along with observation sheets evaluating the quality of teaching materials. The findings show that teachers' comprehension of concepts (±75%), teaching skills (±85%), and the quality of instructional materials (±80%) have all improved a lot. Teachers showed that they could create science lessons that are more meaningful, focused on the student, and encourage critical and reflective thinking. The initiative also made it easier for colleges and universities to work together with teachers by creating a lasting learning community. The results imply that AI-assisted deep learning training is a good way to make science teachers more professional, and it could work well in other areas as well.